Glacial reduction of the North American Monsoon via surface cooling and atmospheric ventilation. Issue 10 (27th May 2017) - Bhattacharya, Tripti; Tierney, Jessica E.; DiNezio, Pedro
Abstract: The North American Monsoon (NAM) provides critical water resources to the U.S. southwest and northwestern Mexico. Despite its importance to regional hydrology, the mechanisms that shape this monsoon are not fully understood. In this paper, we use model simulations of the Last Glacial Maximum (LGM, 21 ka B.P.) to assess the sensitivity of the NAM to glacial boundary conditions and shed light on its fundamental dynamics. We find that atmospheric changes induced by ice sheet albedo reduce NAM intensity at the LGM. The high albedo of the Laurentide ice sheet cools the surface and drives anomalous northwesterly winds that reduce the monsoon circulation and import cold, dry air into the core NAM region. Our work emphasizes the role of ice sheet albedo rather than topography in driving the atmospheric changes that modulate the glacial NAM, and ties our understanding of the NAM to broader theories of monsoon systems. Key Points: Last Glacial Maximum (21 ka B.P.) ice sheets drive weakening of the North American Monsoon by altering the large‐scale atmospheric flow Cooling resulting from high ice sheet albedo weakens the monsoon flow and favors the import of cold, dry air into the monsoon region Modeled glacial response of the North American Monsoon is primarily driven by the atmospheric circulation rather than oceanic changes